Tutorials in university students with a disability - Joaquín Gairín Sallán; José Luís Muñoz Moreno (Pontificia Universidad Católica del Perú, 2013)
This article places an emphasis on the importance of tutorials for students with a disability in universities. It presented the most significant results of the study of tutorials carried out in help services, units or offices for students with a disability inmore than 45 Spanish universities, in relation to promotion, reception, completion and graduation. The contributions highlight the importance of organising a response through a Tutorial Action Plan made up of the stages of motivation and awareness-raisin, planning, execution, evaluation and institutionalisation. Among the principle conclusions, the importance of moving towards a truly inclusive university through tutorial activity is highlighted, thereby providing a guide for providing assistance to university students with a disability.